2023
DOI: 10.3389/fcimb.2023.1153894
|View full text |Cite
|
Sign up to set email alerts
|

Use of probiotic lactobacilli in the treatment of vaginal infections: In vitro and in vivo investigations

Abstract: The vaginal microbiome is a distinct component of the human microbiome that is colonized by a wide variety of microorganisms. Lactobacilli are the most frequently identified microorganisms in the healthy human vagina. These Gram-positive bacilli can acidify the vaginal microenvironment, inhibit the proliferation of other pathogenic microorganisms, and promote the maintenance of a eubiotic vaginal microbiome. However, a vaginal flora with a reduced proportion or abundance of lactobacilli is associated with vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 159 publications
1
17
0
1
Order By: Relevance
“…During the puerperal time, women are at higher risk of vaginal postnatal infections due to the large wound area, as well as other infections such as endometritis when vaginal opportunistic bacteria enter the upper genital tract, or urinary infections 14,44 . Probiotics treatment was already investigated in multiple other studies wo prevent or fight vaginal infections [45][46][47] . It needs to be further investigated how and to what extend administration of probiotics postpartum are capable to accelerate recovery of the postpartum vaginal microbiome Of note, mode of delivery did not appear to affect the postpartum vaginal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…During the puerperal time, women are at higher risk of vaginal postnatal infections due to the large wound area, as well as other infections such as endometritis when vaginal opportunistic bacteria enter the upper genital tract, or urinary infections 14,44 . Probiotics treatment was already investigated in multiple other studies wo prevent or fight vaginal infections [45][46][47] . It needs to be further investigated how and to what extend administration of probiotics postpartum are capable to accelerate recovery of the postpartum vaginal microbiome Of note, mode of delivery did not appear to affect the postpartum vaginal microbiome.…”
Section: Discussionmentioning
confidence: 99%
“…Lactobacillus species, particularly Lactobacillus crispatus , Lactobacillus jensenii , Lactobacillus gasseri , and Lactobacillus iners , are commonly found in healthy vaginal microbiota that plays a crucial role in maintaining vaginal health (Ravel et al ( n.d. )). Probiotic supplements containing these Lactobacillus strains ( L. crispatus DSM32720, L. rhamnosus HN001, L. crispatus LMG S-29995, L. acidophilus GLA-14 and L. crispatus DSM32717) have been shown to effectively restore and maintain a balanced vaginal microbiome by increasing the abundance of beneficial bacteria and reducing the risk of vaginal infections (Liu et al 2023 ). Several clinical studies have demonstrated the efficacy of probiotic interventions in preventing recurrent bacterial vaginosis (BV) and yeast infections (Reid et al 2001 ; Falagas et al 2006 ).…”
Section: Probiotic Interventions: Strategies For Harmonizing the Vagi...mentioning
confidence: 99%
“…In addition to preventing vaginal infections, probiotics may also have therapeutic potential in managing other vaginal dysbiosis-related conditions, such as vulvovaginal candidiasis (VVC) and aerobic vaginitis (AV) (Liu et al 2023 ). Probiotic strains with antimicrobial properties can compete with and inhibit the growth of pathogenic microorganisms, restoring microbial balance and alleviating symptoms associated with these conditions (Plaza-Diaz et al 2018 ).…”
Section: Probiotic Interventions: Strategies For Harmonizing the Vagi...mentioning
confidence: 99%
See 1 more Smart Citation
“…However, these treatments can exacerbate vaginal dysbiosis, which is already present in vaginal infections, potentially disrupting the delicate balance of the vaginal microbiota by affecting beneficial microorganisms ( Bradshaw et al, 2006 ; Schuyler et al, 2016 ). In contrast, probiotics can promote the recovery process by restoring the vaginal microbiota’s environment ( Liu et al, 2023 ). Lactobacilli , recognized for their capacity to maintain an acidic microenvironment through lactic acid production, play an essential role in this intricate microbial community by impeding the growth of detrimental microbes ( Wu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%